2014
DOI: 10.1037/a0035696
|View full text |Cite
|
Sign up to set email alerts
|

Peers increase adolescent risk taking even when the probabilities of negative outcomes are known.

Abstract: The majority of adolescent risk taking occurs in the presence of peers, and recent research suggests that the presence of peers may alter how the potential rewards and costs of a decision are valuated or perceived. The current study further explores this notion by investigating how peer observation affects adolescent risk taking when the information necessary to make an informed decision is explicitly provided. We used a novel probabilistic gambling task in which participants decided whether to play or pass on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 9 publications
9
131
5
1
Order By: Relevance
“…16 For example, the temptation for adolescents to engage in high-risk activities can increase when with friends, even if the adolescent is cognitively aware of potential negative consequences. 40 Therefore, although adolescents generally possess more developed EF skills than younger children, they are also required to negotiate more complex contexts that test such skills to a greater degree; the failure of EF skills in such settings may therefore be particularly costly to an adolescent’s health. 41,42 …”
Section: Development Of Efmentioning
confidence: 99%
“…16 For example, the temptation for adolescents to engage in high-risk activities can increase when with friends, even if the adolescent is cognitively aware of potential negative consequences. 40 Therefore, although adolescents generally possess more developed EF skills than younger children, they are also required to negotiate more complex contexts that test such skills to a greater degree; the failure of EF skills in such settings may therefore be particularly costly to an adolescent’s health. 41,42 …”
Section: Development Of Efmentioning
confidence: 99%
“…Specifically, adolescents are more likely to make risky decisions (Gardner and Steinberg, 2005; Smith et al, 2014) and are more sensitive to immediate reward (O’Brien et al, 2011; Weigard et al, 2014) when knowing that they are being observed by peers than when they are alone. It has been suggested that these effects appear because the presence of peers can constitute a social reward that can bias decision making, presumably through the modulation of the reward system in the brain (Chein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 131 junior high school male students (aged 14–15 years old) performed a roulette task, similar to the one used in a previous study (Smith et al, 2014), implemented on smartphone devices. Participants were presented with a series of roulette wheels showing the probability of gain and loss, and decided whether to ‘play’ or ‘pass’ for each wheel.…”
Section: Introductionmentioning
confidence: 99%
“…While the experimental social psychology literature has a multitude of studies that examine peer influence on various behavioral outcomes (see Paternoster et al 2013 for an overview), the outcomes of interest are often not comparable to (minor) delinquent acts. Similarly, developmental research has also conducted studies on the influence of (deviant) peers on risk-taking behavior or risky decision-making behavior (e.g., Gardner and Steinberg 2005;MacLean et al 2014;Smith et al 2014;van Hoorn et al 2016). However, these studies manipulated either the presence of peers or their risk-aversive attitudes, but not their actual deviant behavior.…”
Section: Previous Experimental Research On Peer Deviancymentioning
confidence: 99%